Teachers’ perceptions of principals’ instructional leadership roles and practices - Ghavifekr, Simin; Radwan, Omaymah; Joseph M. Velarde (Penerbit Universiti Kebangsaan Malaysia, 2019)
As a part of Malaysia’s education transformation, the Ministry of Education expects all principals to be instructional leaders. In response to this call, this study attempts to describe teachers’ perceptions on instructional leadership roles and practices of principals, as well as examine the relationship between the teachers’ gender and their perception of instructional leadership roles and practices. A total of 105 primary school teachers from five primary schools in Alor Gajah, Malaysia participated in this quantitative study. The data was collected randomly through distribution of a survey questionnaire containing 35 items adapted from the Principal Instructional Management Rating Scale (PIMRS). Both descriptive and inferential statistics were used to analyze data using SPSS (V.22). Results from teachers’ responses reveal the following: 1) a moderate level of perception of instructional leadership functions related to defining the school’s mission; 2) a moderate level of perception of functions related to managing instructional program; 3) a low level of perception of functions with respect to promoting a positive climate; and 4) no relationship between gender and the perception of instructional leadership. The results from this study will bring forth the current state of instructional leadership in Malaysian primary schools and keep the Malaysian government abreast with this scenario to improve training programs and make continuous training in principal leadership compulsory.